2017
DOI: 10.22444/ibvs.6211
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of {delta} Sct type pulsations in the eclipsing binary IK Vir

Abstract: We report the detection of δ Sct type variations in the eclipsing binary system, IK Vir (V=11.54 mag, A6, P orb = 0.72 d, Velichko et al. 1991 andKazarovets et al. 1993), in our V-band photometry. The observations were carried out with Moravian G2-1600 CCD camera attached to 28 cm Schmidt-Cassegrain telescope at Akazawa Funao Observatory. Total observational runs are twenty one nights from March 26 to May 26 in 2015. IK Vir is measured differentially to BD+02 2522 = GSC 0281-0223 as the comparison star. BD+02 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The latter authors obtained simultaneous Strömgren uvby light curves of RZ Cas. These authors present a detailed photometric analysis for both binarity and pulsation, deriving WD (Wilson & Devinney 1971) solutions in the four mentioned passbands as well as absolute parameters of both components, and confirming the pulsational behaviour of the primary component as found by Ohshima et al (1998). We use the radii and flux ratios between the components derived by Rodríguez et al (2004) as a reference in our spectroscopic investigation.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The latter authors obtained simultaneous Strömgren uvby light curves of RZ Cas. These authors present a detailed photometric analysis for both binarity and pulsation, deriving WD (Wilson & Devinney 1971) solutions in the four mentioned passbands as well as absolute parameters of both components, and confirming the pulsational behaviour of the primary component as found by Ohshima et al (1998). We use the radii and flux ratios between the components derived by Rodríguez et al (2004) as a reference in our spectroscopic investigation.…”
Section: Introductionsupporting
confidence: 70%
“…A partial eclipse is observed during primary minimum (Narusawa et al 1994). The primary was found by Ohshima et al (1998Ohshima et al ( , 2001 to exhibit short-period light variability with a dominant oscillation mode of a frequency of 64.2 c d −1 . This finding was later confirmed from dedicated multi-site photometric campaigns by both Mkrtichian et al (2003) and Rodríguez et al (2004).…”
Section: Introductionmentioning
confidence: 93%
“…The V light curve fit gives a relation of (m − M) V = 14.8 for OS And. We plot the distance-reddening relations in Figure 25 Ohshima (1988) and IAU Circular Nos. 4493, 4511, and 4524, and the visual data are from the AAVSO archive.…”
Section: V446 Her 1960mentioning
confidence: 99%
“…4493, 4511, and 4524, and the visual data are from the AAVSO archive. We shift the B − V and U − B data of IAU Circulars down by 0.1 and 0.2 mag, respectively, to match these data to those of Ohshima (1988). QV Vul is a dust-blackout type moderately fast nova with t 2 = 50 and t 3 = 53 days (Downes & Duerbeck 2000).…”
Section: V446 Her 1960mentioning
confidence: 99%
“…Obtaining observations of PMHs are rare and often up to chance since they are usually very short lived -only a fraction of the rise time, which in itself is short (e.g., Starrfield et al 1972;Prialnik et al 1978;Prialnik 1986;Shara 1989;Prialnik & Kovetz 1995;Bode & Evans 2012). The rise time is relatively longer for slower developing novae, thus PMHs, in the form of a short plateau, are more commonly found in slow novae, such as V1548 Aql (Kato & Takamizawa 2001;Primak & Pavlenko 2003), HR Del (Terzan 1970;Drechsel et al 1977;Friedjung 1992), V723 Cas (Hirosawa et al 1995;Ohsima et al 1996;Iijima et al 1998) and V5558 Sgr (Munari et al 2007;Naito et al 2007;Poggiani 2008;Tanaka et al 2011). A PMH was also observed in the fast nova, V463 Sct (Kato et al 2002;Poggiani 2018), which is rarely observed.…”
Section: Introductionmentioning
confidence: 99%